Th. Adorno on Mass Art and on Elitarian Art - Valentinavičius, Virginijus (Problemos, 1988)
The article deals with Th. Adorno’s division of art into the mass art and the elitarian art. The influences of G. Hegel and K. Marx on T. Adorno’s philosophy in general and the impact of Hegelian theory of possibility and reality in particular are traced back. The exclusively negative character of Th. Adorno’s criticism of bourgeois culture is pointed out as a sign of its weakness.